0193 Prediction of mental outcomes by early conditions after occupational injuries. (23rd June 2014) - Guo, Leon; Lin, Kuan-Han; Guo, Nai-Wen; Shu-Chu Shiao, Judith; Liao, Shih-Cheng; Hu, Pei-Yi; Hsu, Jin-Huei
Abstract : Objectives: Psychiatric diseases have been an important complication after occupational injuries. This study aimed to determine early factors predicting psychological health outcomes at twelve months after occupational injuries. Method: The study candidates were workers who sustained occupational injuries and were hospitalised for 3 days or longer in 2009. A self-reported questionnaire was sent to them at three months after injury. The questionnaire inquired about demographics, severity of injury, working status, personal factors, as well as included a psychometric instrument Brief Symptom Rating Scale (BSRS-50). At one year, all participants were invited again to complete a questionnaire including BSRS-50. Results: A total of 853 workers completed the questionnaire at three months and 12 months after injury. Among them, 84 (9.3%) had general severity index (GSI) of 70 or higher at 12 months after injury, indicating poor psychological condition. Using multivariate logistic regression analysis for mutual adjustment, predictive factors for elevated GSI were found to include dismemberment or affected physical appearance (OR 1.7, 95% CI 1.0–3.1), BSRS at 3 months after injury (OR 8.8, 95% CI 5.4–14.4), and having to leave original workplace (OR 2.5, 95% CI 1.4–4.3). The findings indicated that severity of injury, early psychological condition, and workplace accommodation to allow returning to original workplace are important factors for later psychological health after occupational injury. Conclusions: Among workers sustaining occupational injuries, psychological condition could have been affected at 12 months after injury. Predictors of the psychological condition were identified, to allow for possibility of early intervention.